Development and validation of RRLC–UV method for determination of chlorogenic acid in green coffee - Velkoska-Markovska, Lenche; Jankulovska, Mirjana S.; Petanovska-Ilievska, Biljana; Hristovski, Kristijan (Akademiai Kiado Zrt., 2020)
Coffee is one of the most widely consumed beverages in the world. It contains many bioactive compounds, including chlorogenic acid which possesses various biological properties. In this study, in order to determine concentration of chlorogenic acid in green coffee, a reverse-phase rapid resolution liquid chromatography (RP-RRLC) method with diode-array detection (DAD) was developed. Successful separation was achieved on a Poroshell 120 EC-C18 (50 mm × 3 mm; 2.7 μm) column using acetonitrile–water with 1% phosphoric acid (10:90, v/v) as a mobile phase, at a flow rate of 1 mL/min, and with UV detection at 325 nm. The identification was made with comparison of the retention time of pure analytical standard with the retention time of chlorogenic acid in the analyzed samples. The developed method was validated using the following parameters: linearity, sensitivity, selectivity, precision, and accuracy. Excellent linearity over the range 12.33–143.50 μg/mL was achieved with R2 values greater than 0.99. The intra-day precision was validated with the %RSD values, which confirmed that the method for determination of chlorogenic acid was repeatable. The mean recovery rate of the method ranged between 97.87% and 106.67% with %RSD values lower than 1%. The limit of detection and limit of quantification values under the used chromatographic conditions were 0.29 and 0.96 pg, respectively. This method was successfully employed for quantitative determination of chlorogenic acid in green coffee samples.
Keywords: chlorogenic acid, RP-RRLC, green coffee, extraction, separation, method validation